Plant, herbivore and parasitoid community composition in native Nothofagaceae forests vs. exotic pine plantations. Issue 3 (5th January 2018) - Peralta, Guadalupe; Frost, Carol M.; Didham, Raphael K.
Abstract: Converting natural areas into land used for production causes dramatic changes in the configuration of landscapes. Both the loss and fragmentation of native habitats contribute to biodiversity loss world‐wide and the consequent creation of artificial edges can have a significant influence on community assembly. The conservation value of plantation forests has been identified for specific species, but it is not clear whether exotic pine plantations can also be used for the preservation of native communities in general. We studied whether community composition of different trophic levels (plants, herbivorous caterpillars, parasitoids) changed across native Nothofagaceae forests to exotic pine plantations, and whether habitat edges affected communities differently depending on the forest type considered. To accomplish this, we sampled plants, herbivorous caterpillars and parasitoids in native Nothofagaceae and exotic pine plantation forests and compared community composition of each trophic level across habitats. We found that community composition of plants, herbivorous caterpillars and parasitoids differed significantly between native and exotic plantation forests, and that variation in the composition of the upper trophic levels was strongly dependent on variation in the composition of the lower trophic level. Moreover, differences in community composition were mostly the result of species turnover, suggesting that plantations are complementary habitats for some species, but cannot be a substitute habitat for all native forest species. Furthermore, edge effects had a strong impact on the composition of native communities, such that certain species were only present in the interior of the native habitat. Synthesis and applications . Large areas of native vegetation, where the interior remains intact, are essential to preserve species that are susceptible to edge effects and that cannot occupy other habitat types. Creating straight instead of winding edges could decrease the impact that plantations have on native forests. Furthermore, increasing the representativeness of native plant communities in exotic plantation forests would cascade up to higher consumer trophic levels, considerably increasing the conservation value of these commercial stands. Abstract : Large areas of native vegetation, where the interior remains intact, are essential to preserve species that are susceptible to edge effects and that cannot occupy other habitat types. Creating straight instead of winding edges could decrease the impact that plantations have on native forests. Furthermore, increasing the representativeness of native plant communities in exotic plantation forests would cascade up to higher consumer trophic levels, considerably increasing the conservation value of these commercial stands.